ANALISIS FAKTOR EKONOMI TERHADAP TINGKAT KEMISKINAN DI KOTA SEMARANG - Widyawati, Retno Febriyastuti; Setiyani, Mei Handriati (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
Poverty is a complex social and economic problem. This poverty problem also occurs especially in urban areas, such as Semarang City, which acts as the capital city of Central Java Province and is the center of regional economic growth. Although this city has a strategic role, there are still a large number of people living below the poverty line. Poverty remains an issue that needs serious attention from various parties. This study aimed to analyze economic factors that affect the poverty rate in Semarang City for the period 2011-2023. The independent variables studied include the Labor Force Participation Rate (TPAK), Human Development Index (HDI), and Gross Regional Domestic Product (GRDP), with the poverty rate as the dependent variable. The analysis method used is multiple linear regression with the Ordinary Least Squares (OLS) approach, using secondary data from the Central Statistics Agency. The study results show that TPAK has a positive coefficient and a significant effect on the poverty rate. HDI has a negative coefficient and significantly affects the poverty rate. GRDP has a positive coefficient and does not significantly affect the poverty rate. Based on these findings, the Semarang City Government should focus on improving the quality of human resources through education and skills training relevant to the labor market's needs. In addition, efforts are needed to ensure that economic growth can be enjoyed by all levels of society so that poverty reduction policies will be effectiveKata Kunci: angkatan kerja, ekonomi, kemiskinan, vokasional